Tugas Analisis Peran Guru dalam Menghadapi Siswa Sekolah SD Pelangi yang Berkebutuhan Khusus - Ezra, Meilinda; Latifah, Arfita Husnul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Every child has equal potential, but education and environment influence their development. Family support is essential for comfortable learning, especially for children with special needs (ABK) who require a special approach. Unfortunately, stigma often equates individuals with disabilities, even though their needs are unique. Based on Government Regulation Number 13 of 2020, the government is required to provide inclusive education for people with disabilities, including facilities, infrastructure, and special educators. In inclusive education, the curriculum is adjusted to the needs of ABK for flexibility in materials, processes, and learning evaluations. In the past, ABK studied in Special Schools (SLB), but now many public schools accept them. This system allows them to learn with peers with the support of special assistant teachers (GPK) who help overcome learning barriers, support interactions, and optimize their potential. This research was conducted at SD Pelangi Anakku, Jalan Villa Mutiara Pluit Blok C6, Periuk, Tangerang City, Banten, on October 18, 2024. Using a descriptive qualitative approach, the researcher described the real conditions in the field. Data were collected through interviews, observations, and documentation. Data analysis in this study used the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The researcher structured the interview for informants with several focuses: 1) The motivation for the ABK program at SD Pelangi is the belief that all children have the right to receive a decent education, 2) Parental involvement through regular meetings for child development, 3) Types of ABK in the class include intellectual disabilities, autism, and learning disorders, assisted by two assistant teachers, and 4) Independent Curriculum which is adapted for ABK. Assistant teachers play an important role in supporting slow learner students, both inside and outside the classroom, with attention to understanding the material, assessment, and social interaction.